INVESTIGATIVE STUDY OF THERMAL PERFORMANCE OF THERMOSYPHON SOLAR COLLECTOR - K. Jasim, Ayoob; H. Abbood, Basim; H . Alhamdo, Mohammed (Journal of Engineering and Sustainable Development, 2021)
Experimental and Numerical investigation has been performed to improve the thermosyphon thermal performance. Optimization process concentrated on both the water and the operating liquid temperature inside the tank and the thermosyphon. For this purpose, three different models of improvement methods have been studied that depend on increasing the surface area with no changing in the volume of operating liquid. The first one (case-A-) is by add ten ring fins about the absorber pipe. The second method (Case-B-) is by add twenty ring fins about the absorber pipe. While, the third way (Case-C-) is by add ten ring fins with ten grooves about the absorber pipe. The thermosyphon thermal performance was compared between the traditional model and experimental model. Moreover, numerical simulate for all cases were done with computational fluid dynamic (CFD), ANSYS 19.R3. It was observed through the results that a good convergence between the numerical and, experimental results. Furthermore, the thermal performance for case-A- is found greater than all other cases under study.